Politeness Strategies Seen in Customers’ Reviews of The Plaza New York Hotel on Booking.com - Michelle Nikita Prakasa (Kata Kita: Journal of Language, Literature, and Teaching, 2025)
This qualitative research aims to see the types of politeness strategies used in the customers’ reviews (good and poor) of The Plaza New York hotel on Booking.com. This research uses Brown and Levinson’s (1987) theory about politeness strategies, as cited in O’Keeffe et al. (2011). The customers’ reviews the writer uses are the newest ones on Booking.com, from January 2024 to February 2025. The data collected are 20 good and 10 poor reviews containing politeness strategies. The writer finds that both data use all types of politeness strategies, however, poor customers’ reviews use only one sub-strategy in Negative Politeness (Don’t presume/assume). The good customers’ reviews use Bald on Record and Off Record to convey their disappointment, while poor customers’ reviews use Positive Politeness and Negative Politeness to deliver their praises. The writer suggests that other researchers interested in politeness strategies can investigate other fields and use other theories to be more focused on the culture that influences the customers’ choices of politeness strategies.